Epistemic Communities and Public Support for the Paris Agreement on Climate Change. (December 2021) - Maliniak, Daniel; Parajon, Eric; Powers, Ryan
We study how informing the public about the views of international policy experts shapes public support for international cooperation. Using survey experiments, we test whether variation in levels of support among experts with differing types of domain-specific knowledge can shape public support for a recent and politically salient international treaty: the UNFCCC COP21 Paris Climate Agreement. Our results show that the public is, under certain conditions, deferential to the views of experts, with respondents reporting increasingly higher levels of support for the COP21 agreement as support among experts increased. In addition, we provide suggestive evidence that domain-specific expertise matters: When it comes to support for the COP21 agreement, the public is most sensitive to the views of climate scientists, while exposure to the views of international relations and international economics experts have less dramatic and less consistent effects. Despite these results, we find that it is exposing the public to information about opposition to a proposed treaty among members of relevant epistemic communities that has greatest and most consistent effects. Our findings thus provide new insight into the conditions under which epistemic communities can shape public support for particular policy alternatives.